Nurses' experiences of pain management for people with advanced dementia approaching the end of life: a qualitative study. Issue 9 (7th February 2017) - De Witt Jansen, Bannin; Brazil, Kevin; Passmore, Peter; Buchanan, Hilary; Maxwell, Doreen; McIlfactrick, Sonja J; Morgan, Sharon M; Watson, Max; Parsons, Carole
Abstract : Aims and objectives: To explore hospice, acute care and nursing home nurses' experiences of pain management for people with advanced dementia in the final month of life. To identify the challenges, facilitators and practice areas requiring further support. Background: Pain management in end‐stage dementia is a fundamental aspect of end‐of‐life care; however, it is unclear what challenges and facilitators nurses experience in practice, whether these differ across care settings, and whether training needs to be tailored to the context of care. Design: A qualitative study using semi‐structured interviews and thematic analysis to examine data. Methods: Twenty‐four registered nurses caring for people dying with advanced dementia were recruited from 10 nursing homes, three hospices and two acute hospitals across a region of the UK. Interviews were conducted between June 2014–September 2015. Results: Three core themes were identified: challenges administering analgesia, the nurse–physician relationship, and interactive learning and practice development. Patient‐related challenges to pain management were universal across care settings; nurse‐ and organisation‐related barriers differed between settings. A need for interactive learning and practice development, particularly in pharmacology, was identified. Conclusions: Achieving pain management in practice was highly challenging. A number of barriers were identified; however, the manner and extent to which these impacted on nurses differed across hospice, nursing home and acute care settings. Needs‐based training to support and promote practice development in pain management in end‐stage dementia is required. Relevance to clinical practice: Nurses considered pain management fundamental to end‐of‐life care provision; however, nurses working in acute care and nursing home settings may be undersupported and under‐resourced to adequately manage pain in people dying with advanced dementia. Nurse‐to‐nurse mentoring and ongoing needs‐assessed interactive case‐based learning could help promote practice development in this area. Nurses require continuing professional development in pharmacology.